Infections in Patients Receiving Ibrutinib for Treatment of Lymphoma: A Single-center Experience. (4th October 2017) - Varughese, Tilly A; Redelman-Sidi, Gil; Cohen, Nina; Seo, Susan K; Hohl, Tobias M
Abstract: Background: Ibrutinib is an inhibitor of Bruton's tyrosine kinase (BTK), a key kinase in the B-cell receptor pathway that plays a significant role in the survival of B-cells. Ibrutinib has been approved for the treatment of several B-cell malignancies. Recently, a few cases of opportunistic infection in patients receiving Ibrutinib therapy have been reported. We aimed to determine the scope of infection in patients with lymphoid malignancies who received treatment with Ibrutinib. Methods: Retrospective review of patients with lymphoid malignancies who received at least 30 consecutive days of Ibrutinib (monotherapy or combination) from December 2012–December 31, 2016. Infections were defined based on Infectious Diseases Society of America (IDSA) criteria and revised 2008 European Organization for Research and Treatment of Cancer/Invasive Fungal Infections Cooperative Group (EORTC) guidelines. Charts reviewed for a minimum of 6 months to determine development of infection. Results: Charts of 250 patients who received treatment with Ibrutinib were reviewed. Thirty-six excluded as they were lost to follow-up or received less than 30 days of Ibrutinib therapy. Among the 214 patients included, mean age was 65 (range 31–92) years and 161 (75%) were men. Eleven patients (5.1%) developed infection during the follow-up period: six cases of invasive aspergillosis (IA) (six pulmonary and one also involved the central nervous system (CNS)), twp cases of methicillin-resistant Staphylococcus aureus pneumonia, one case of CNS cryptococcal meningitis, one PJP Pneumonia, and one disseminated zoster (CNS meningoencephalitis). Of the 11 patients who developed infection, none was neutropenic at the time of infection and none received substantial corticosteroid courses. Apart from one patient who received combination therapy with ofatumumab, all patients who developed infection were receiving Ibrutinib monotherapy prior to the onset of infection. Conclusion: Our data demonstrate that patients receiving Ibrutinib therapy for lymphoid malignancies are at risk for serious infections, including invasive fungal infections. The majority of infections in these patients developed in the absence of other risk factors for infection, suggesting that Ibrutinib may be independently associated with increased risk for certain infections. Disclosures: All authors: No reported disclosures.